Pengaruh Rasio Keuangan dan Good Corporate Governance terhadap Kinerja Keuangan - Lestarina, Utami Fahmi; Ramdan, Nurul Amalia; Aziz, Aghni Aulia; Sugiharti, Harpa (J-MAS (Jurnal Manajemen dan Sains), 2025)
This research was conducted to evaluate and examine the impact of profitability, sales growth, and firm size on financial performance in Food and Beverage companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The sampling technique applied in this study was purposive sampling, which involves selecting samples based on specific criteria to sharpen the research focus. Based on this purposive sampling method, there were 14 Food and Beverage companies listed on the Indonesia Stock Exchange (IDX), with a total of 70 data points collected over five years. The data source used in this research was annual reports. The data analysis methods employed were multiple linear regression analysis, descriptive statistical analysis, classical assumption testing, and hypothesis testing. After conducting the tests, the results revealed that profitability ratio and firm size have a positive and significant impact on companies’ financial performance, while sales growth ratio shows no significant influence on company performance. Therefore, it can be concluded that profitability ratio and firm size play a crucial role in determining financial performance, whereas sales growth ratio does not make a meaningful contribution in this regard.